POLYGALA PANICULATA L. SEBAGAI ALTERNATIF TANAMAN OBAT DI TAMAN OBAT KELUARGA - Sutomo, Sutomo (Buletin Udayana Mengabdi, 2012)
Abstract Polygala paniculata L. grows naturally in grasslands, open woodland or even in our own backyard. But most people only see P. paniculata as a weed or wild grass instead of a medicinal plants. This paper is going to discuss about a profile of P. paniculata in order to promote this species as a medicinal plant.